Multi-phased scaffolds derived from decellularized extracellular matrices for tendon-to-bone interface tissue engineering - Alom, Noura (2017)
The tendon-to-bone interface exhibits gradients in tissue organization, with variation in chemical, physical and biological properties for each. After injury, a mechanically weaker and structurally disorganized tissue is formed. Tissue engineering approaches have focused on developing and investigating tissue-engineered scaffolds to replicate the native biological, structural, and mechanical features of the tendon-to-bone interface site. The idealized technique for regenerating the interface is to design a multi-phased scaffold with multiple zones, and multiple cell types to functionally restore the structural, cellular, and mechanical properties of the tendon-to-bone interface. Hydrogel scaffolds derived from the extracellular matrix (ECM) of mammalian tissues have been successfully used to promote tissue repair in vitro and in vivo. In this study, ECM hydrogels prepared from demineralized and decellularized bovine bone were investigated to evaluate the osteoinductive properties of these hydrogels in the presence and absence of osteogenic medium, and their ability to act as a carrier for local delivery of cells and growth factors. Decellularized bone matrix (bECM) hydrogels stimulated osteogenic differentiation in C2C12 mouse myoblast cells and mouse primary calvarial cells (mPCs) even in the absence of osteogenic medium. Moreover, these hydrogels demonstrated stable release of human serum albumin (HSA); the release kinetics of proteins from hydrogels was dependent on bECM hydrogel concentration. Hydrogels derived from decellularized equine tendon extracellular matrix were also prepared; decellularized tendon matrix (tECM) hydrogels had distinct structural and biological properties and it supported human mesenchymal stem cells (hMSCs) attachment and proliferation. tECM enhanced hMSCs tenogenic differentiation and suppressed osteogenic differentiation, while the presence of bECM greatly induced hMSCs osteogenic differentiation and suppressed tenogenic differentiation. An electrospun scaffold was produced using decellularized bovine bone extracellular matrix (bECM), to contribute to multi-phased scaffold design, and to present this unique ECM material in a new advanced form. In the present research, we optimised a method to electrospin decellularized bovine bone extracellular matrix (bECM) without the addition of any other materials as a potential improvement for cell adhesion, proliferation and differentiation. bECM was dissolved in 50/50 1, 1, 1, 3, 3, 3-Hexafluoro-2-propanol/Trifluoroacetic acid. A high voltage was applied to the bECM solution and fibers were collected as a uniform mesh, the solutions were electrospun for 3 hours at 20°C in 40% relative humidity. We assessed the biological activity and osteogenic capability in vitro of electrospun bECM scaffolds in comparison to electrospun gelatin scaffolds using mouse primary calvarial cells (mPCs) and human mesenchymal stem cells (hMSCs).